ANALISIS RASIO KESEHATAN BANK UMUM KONVENSIONAL DI INDONESIA PERIODE 2016-2020 - Sri Mulyatun; Alexandria Berutu; Anik Sri Widawati (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2022)
Banking is a financial institution that has an important role. The strategic role of banks in supporting the implementation of national development, namely in the context of increasing equitable development, economic growth and stability. Factors that must be considered by conventional commercial banks regarding profitability. Because bank profitability is one of the benchmarks for customers to trust the bank. Bank profitability is in the interest of all parties in order to get high profits. The title of this research is the Analysis of the Health Ratios of Conventional Commercial Banks in Indonesia for the Period 2016-2020. The independent variables used in this research are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL), Operating Cost to Operating Income (BOPO). While the dependent variable used is Return On Assets (ROA). The data used in this study uses secondary data originating from the Indonesian Banking Statistics (OJK) for the 2016-2020 time series. This study uses multiple linear regression analysis techniques using the Ordinary Least Square (OLS) method, with the help of the Eviews version 10 application. The results of this study indicate that the Capital Adequacy Ratio (CAR) shows that it has a negative and insignificant effect of 0.1236% on Return on Assets (ROA) in Conventional Commercial Banks. Loan To Deposit Ratio (LDR) shows that it has a positive and significant effect of 0.0000% on the Return on Assets (ROA) of Conventional Commercial Banks. Non-Performing Loan (NPL) shows that it has a negative and insignificant effect of 0.9694% on the Return on Assets (ROA) of Conventional Commercial Banks. Operating Costs on Operating Income (BOPO) shows that it has a negative and significant effect of 0.0006% on the Return on Assets (ROA) of Conventional Commercial Banks. Based on the coefficient of determination test, the ratio of CAR, LDR, NPL, and BOPO has a simultaneous effect on ROA of Conventional Commercial Banks with a value of 0.681725 or 68.17%.